Klippel Feil Syndrome: Clinical Phenotypes Associated With Surgical Treatment. Issue 11 (1st June 2020) - Hachem, Laureen D.; Mathieu, Francois; Lamberti-Pasculli, Maria; Hanak, Brian W.; Zeller, Reinhard; Kulkarni, Abhaya V.; Drake, James; Ibrahim, George M.
Abstract : Study Design: Retrospective study. Objective: To define distinct Klippel-Feil syndrome (KFS) patient phenotypes that are associated with the need for surgical intervention. Summary of Background Data: KFS is characterized by the congenital fusion of cervical vertebrae; however, patients often present with a variety of other spinal and extraspinal anomalies suggesting this syndrome encompasses a heterogeneous patient population. Moreover, it remains unclear how the abnormalities seen in KFS correlate to neurological outcomes and the need for surgical intervention. Methods: Principal component (PC) analysis was performed on 132 KFS patients treated at a large pediatric hospital between 1981 and 2018. Thirty-five variables pertaining to patient/disease-related factors were examined. Significant PCs were included as independent variables in multivariable logistic regression models designed to test associations with three primary outcomes: cervical spine surgery, thoracolumbar/sacral spine surgery, and cranial surgery. Results: Fourteen significant PCs accounting for 70% of the variance were identified. Five components, representing four distinct phenotypes, were significantly associated with surgical intervention. The first group consisted of predominantly subaxial cervical spine fusions, thoracic spine abnormalities and was associated with thoracolumbar/sacral spine surgery. The second group was largely represented by axial cervical spine anomalies and had high association with cervical subluxation and cervical spine surgery. A third group, heavily represented by Chiari malformation, was associated with cranial surgery. Lastly, a fourth group was defined by thoracic vertebral anomalies and associations with sacral agenesis and scoliosis. This phenotype was associated with thoracolumbar/sacral spine surgery. Conclusion: This is the first data-driven analysis designed to relate KFS patient phenotypes to surgical intervention and provides important insight that may inform targeted follow-up regimens and surgical decision-making. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textKlippel-Feil syndrome encompasses a heterogeneous patient population and it remains unclear how the various associated abnormalities correlate to neurological outcomes and the need for surgical intervention. Using principal component analysis, we identified four distinct patient phenotypes that were significantly associated with surgical intervention.